2003
DOI: 10.1111/1472-9296.00069
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Relations and Human Resource Management Practices in Australian and Overseas-Owned Workplaces: Global or Local?

Abstract: This paper compares human resource (HR)and industrial relations (IR)practices in the workplaces of predominantly Australian and predominantly overseas–owned organisations. It advances understanding of HR/IR in Australia and elsewhere by considering two questions. First,whether Australian–owned workplaces have different HR/IR practices from overseas–owned workplaces. Second,whether there has been a convergence or divergence of practices between the two groups in recent years. The analysis is conducted using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…It was noted that Australia has received comparatively less attention in this area with the notable exception of papers that drew on Cranet data (e.g. Walsh, 2001;McGraw and Harley, 2003), although these did not differentiate between domestic firms and domestic MNCs. Due to the significant changes that occurred in the Australian industrial relations system from the 1980s which promoted greater liberalization and potentially provided firms with greater choice on how they approached employee representation and consultation (Townsend, Wilkinson, and Burgess, 2013), a study like this one is a timely and important contribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was noted that Australia has received comparatively less attention in this area with the notable exception of papers that drew on Cranet data (e.g. Walsh, 2001;McGraw and Harley, 2003), although these did not differentiate between domestic firms and domestic MNCs. Due to the significant changes that occurred in the Australian industrial relations system from the 1980s which promoted greater liberalization and potentially provided firms with greater choice on how they approached employee representation and consultation (Townsend, Wilkinson, and Burgess, 2013), a study like this one is a timely and important contribution.…”
Section: Discussionmentioning
confidence: 99%
“…This led her to suggest that the strongly regulated Australian industrial relations system did not deter innovative practice. Similarly, McGraw and Harley (2003), utilizing two sets of AWIRS data, found that foreign MNCs were using a more sophisticated suite of HR policies and practices compared to domestic firms. Overall, these studies suggest there is substantial scope for firms to introduce novel management practices.…”
Section: Variation or Similarity? Employment Relations In Liberal Marmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst strong consistency in results has failed to materialize across these different studies, the tentative conclusions suggest that HRM in foreign-owned MNEs is different to that in domestic firms (Geary and Roche 2001;McGraw and Harley 2003). More specifically, it appears that whilst foreign MNEs may have to adapt local practices on occasion (e.g., for cultural and legislative/regulatory reasons), overall they appear to be more formal and sophisticated in terms of their HRM practices (Hiltrop 1999;McGraw and Harley 2003) than domestic organizations.…”
Section: Best Practices and Globalization Dominance And Spill-over Ementioning
confidence: 89%
“…In the beginning, multinational companies adopt standardization of human resource management, which believed coherence strategy and coordinate practice can lead to operational effectiveness and efficiency. However, they met difficulties after the international dimension becoming more and more popular as a result of changes in operating environment and structures (McGraw and Harley 2003). Different people in different countries have different culture and conception on organization behavior.…”
Section: Human Resource Challengesmentioning
confidence: 99%